1985
DOI: 10.2214/ajr.144.3.629
|View full text |Cite
|
Sign up to set email alerts
|

Xeromammography after augmentation mammoplasty

Abstract: An 8-year review done of mammography at one institution identified 30 patients who had undergone a previous breast augmentation procedure. Of the 30, six had had silicone injections, 20 silicone-filled implants, and six saline-filled implants. Both free and encapsulated silicone significantly obscured underlying breast tissue because of density and associated calcifications, which would have interfered with detection of subclinical carcinomas. Xeromammography proved useful, however, in clarifying the nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The cystic spaces are relatively small and uniform. Calcifications are in the form of irregular microcalcifications, and small ring-like or large eggshell calcifications (13)(14)(15). These histologic findings of foreign body granulomas induced by liquid silicone might be confused with those of paraffinoma.…”
Section: B Amentioning
confidence: 99%
“…The cystic spaces are relatively small and uniform. Calcifications are in the form of irregular microcalcifications, and small ring-like or large eggshell calcifications (13)(14)(15). These histologic findings of foreign body granulomas induced by liquid silicone might be confused with those of paraffinoma.…”
Section: B Amentioning
confidence: 99%
“…4 The periareolar access is largely used in mammaplasty with low complication rates. [6][7][8] In this procedure, the use of the videoscope is crucial, which is needed in most parts of the procedure, especially when the nipple is anteriorly placed and the mitral valve cannot be seen through the minithoracotomy. The video assistance plays a fundamental role in this approach enabling smaller skin incisions and reducing trauma to the periareolar complex and to the mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to avoid surgical site complications, it is important to perform a careful preoperative evaluation of the breasts. [6][7][8] Young women with incomplete mammogenesis, women in the lactating period, and patients with diagnosed breast nodules are not suitable for the periareolar approach. It may be reasonable to perform preoperative screening with ultrasound or mammography in patients older than 40 years, in search of undiagnosed pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a comparison study of pre-and post-augmentation mammograms in the same patient, even with Eklund's maneuvers, an amount of breast tissue (up to 19%) still could not be examined [45]. Some authors suggested that using all the possible MX projections (standard and with Eklund's maneuvers) had a substantial advantage in identifying more breast abnormalities [46]. Moreover, in patients with large or extra-large breast implants and limited surrounding breast tissue, this technique cannot be performed, considering an increased risk of complications from the implants, such as rupture, due to mammography compression.…”
Section: Mammography (Mx)mentioning
confidence: 99%